AI INTEGRATION IN LEARNING SYSTEMS: LITERATURE REVIEW ANALYSIS ON TEACHING OPTIMISATION THROUGH VIRTUAL TUTORS, DATA ANALYSIS, AND AUTOMATED EDUCATIONAL MATERIAL CREATION - Rizki Fauzi; Novianti Sisilia (CV. ADIBA AISHA AMIRA, 2025)
The development of artificial intelligence (AI) has brought a new paradigm in the world of education by introducing learning systems that are more adaptive, efficient, and learner-centred. This study aims to analyse the role of AI in optimising the learning process through the application of virtual tutors, learning analytics, and the automation of educational material creation. The research method used is library research by reviewing various existing scientific sources. The results show that the integration of AI in education can improve learning personalisation, strengthen data-based decision making, and increase efficiency in academic content development. AI-based virtual tutors enable real-time feedback and individual guidance, while learning analytics help teachers understand students' needs more accurately. On the other hand, the automation of teaching material creation using generative technology increases teachers' time effectiveness and expands access to relevant and contextual learning resources. However, the implementation of AI requires serious attention to ethical issues, data validity, and potential algorithmic bias so that this technology can truly be beneficial in a fair and sustainable manner. This study emphasises that collaboration between human intelligence and artificial intelligence is key to building an innovative, inclusive, and meaningful future education ecosystem.